RESPONSE OF PHYSIOLOGICAL AND HISTOLOGICAL TRAITS TO ENZYME SUPPLEMENTATION AND SOAKING OF DIETS CONTAINING CORN AND WHEAT OF THE LAYNING HENS - & et al., Al Rubaee (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted at Poultry Research Station Animal Resources Research Department–State Board of Agricultural Research/ Ministry of Agriculture in Abu Ghraib, which included two experiment to study the effect of enzyme supplementing and soaking to the diets of the laying hens containing corn and wheat on productive performance.Three hundred Brown-egg hens (ISA Brown) 40 weeks of age were used in this experiment after preliminary period for two weeks. Layer hens distributed randomly to ten treatments with 2 replicates (15 hens per replicate); and fed on diets according to the age periods in ISA guide. Treatments were as follows: T1: Control group (100% corn).T2: 100% corn with soaking. T3: 100% corn with enzymes. T4:100% corn with soaking and enzymes. T5: 33% corn replacement wheat with soaking. T6: 33% corn replacement wheat and with enzymes. T7: 33% corn replacement wheat with soaking and enzymes. T8: 66% corn replacement wheat with soaking. T9: 66% corn replacement wheat with enzymes. T10: 66% corn replacement wheat with soaking and enzymes. The results showed a significant increase (P<0.05) in The levels of serum blood calcium for T10, and serum blood phosphorus in T8,T10 while the inorganic phosphorus in feces for all treatments was lower than the control treatment. There are no significant differences between all treatments Calcium and Phosphorus in tibia bone. were lower than the control treatment in cholesterol levels in blood serum. No differences were noticed for crypts depth between all treatments, while T3, T6, T7, T8 ,T9 ,T10 showed a significant decrease (P <0.05) for the length of villi. So it was concluded that Enzyme supplementation and soaking to the diets of the laying hens significantly increased blood serum characteristics and also minimize the feces P by enhancing phytic acid breaking. it also increased villi length in small intestine which lead to better food digestion and absorption